The Study of Entrepreneurship and Innovation Adoption by Farmer in Improving Lowland Rice Farming - Muhammad Fauzan Umar; Iwan Nugroho; Darmadji Darmadji; Suwarta Suwarta (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2020)
The study of entrepreneurship and the adoption of innovations in farming so far shows a one-sided approach using a single equation model. It is not able to explore more in-depth information to improve farm management. This study aims to study (i) the performance of farming, (ii) the role of entrepreneurship and the adoption of innovative tractor use, and (iii) find the relationship between entrepreneurship, adoption of innovation, and the application of cultivation technology to the performance of lowland rice farming. The study was conducted in the village of Mattiro Ade, Patampanua sub-district, Pinrang Regency, South Sulawesi province. The survey was done on 50 lowland rice farmers who applied the tractor and combine harvester technology. The study uses a descriptive approach and the method of path analysis (partly least square). The results showed that the technology of tractor and combine harvester could improve farming performance, with an average yield of 6.62 tons of rice per hectare, a profit of 21.9 million rupiahs per hectare, with an R/C ratio of 3.21. Farmers exhibit perceptions of entrepreneurship and technology adoption at moderate levels. Farmers show limitations in access to information, loans or venture capital, and training in the use of tractors. The adoption of innovations by farmers deals with obstacles in terms of tractor operations, tractor prices, and the weak role of farmer groups. Entrepreneurship and technology adoption have a significant role in increasing the performance of lowland rice farming, where technology plays a role as an intervening variable. This research has important implications, namely the provision of extension workers and the empowerment of farmer groups to facilitate technology adoption and increase entrepreneurial entrepreneurship in farm management.JEL Classification: L26, O35, Q12